Analysis of Electrical and Thermal Conductivities of blended Clamshell Powder, Kaolin and CuO Ceramics - Nurzahziani .; suhrawardi Ilyas; Zulfalina . (Journal of Aceh Physics Society, 2014)
The electrical and thermal analysis of blended clamshells powder, kaolin, and CuO ceramics have beenconducted. Clamshell is used in the experimentation due to its high CaCO3 that is about 96-98%. Theresearch is aimed to analyze the effect of CuO addition on clamshell powder-and-kaolin mixed ceramics andto observe the electrical and thermal properties of its. CuO concentration was varied up to 10% (weight).We found that the samples could not set and directly disintegrate under the exposure to cold air when baked at temperature higher then 600°C. 8% addition of CuO to white shell gave a more stable sample and recorded 2,17 x 10-7 S/cm electrical conductivity and 0,9977 W/m°C thermal conductivity. There was a trend that those two conductivities are increasing over a large CuO concentration and kept increasing. Based ongeneral classification, this sample is considered to be semiconductor and its thermal conductivity is larger than glass. Semiconductors are very important in electronic manufacturing sector and this material shows the capability of tailoring its conductance. XRD analysis tells that CuCO3bonding has been initiated in the mixture.